Deprescribing drugs with anticholinergic effects in older patients with increased risk of dementia in the multicomponent intervention study AgeWell.de - Lepenies, Laura; Seidling, Hanna; Pabst, Alexander; Luppa, Melanie; Döhring, Juliane; Williamson, Martin; Frese, Thomas; Gensichen, Jochen; Hoffmann, Wolfgang; Kaduszkiewicz, Hanna; König, Hans-Helmut; Thyrian, Jochen René; et al. (British journal of clinical pharmacology, 2025)
Aim: Drugs with anticholinergic effects are often considered as potentially inappropriate medications, especially for older patients, and deprescribing such drugs may improve cognitive function. The aim was to investigate the effectiveness of counselling on drug risks as part of a multimodal intervention to prevent cognitive decline. Methods: The AgeWell.de study, a multi-centre, cluster-randomized controlled study, was conducted in 123 German general practices between June 2018 and January 2022. The study included a multicomponent intervention programme for patients at increased risk of dementia, delivered over a 2-year period. As part of the medication optimisation intervention, patient data and medication records were screened to identify medication risks and provide recommendations to general practitioners. Results: In total, 808 patients with complete data were included in the present analysis (intervention group = 374, control group = 434). At baseline, 132 (16.8%) patients had at least one anticholinergic prescription. After 2 years, approximately one-third of these patients no longer received drugs with anticholinergic effects. There were no significant differences between the intervention and control groups, with 67.6% and 72.1%, respectively, continuing to take drugs with anticholinergic effects (P = 0.57). Patients reported anticholinergic symptoms more frequently when taking any medication (5.0% vs 33.8%), and even more so when taking drugs with anticholinergic effects (56.1%). Deprescribing of all drugs with anticholinergic effects was non-significantly higher in patients who reported at least one anticholinergic symptom compared to patients without any anticholinergic symptoms (58.6% vs 54.1%). Conclusion: The medication optimisation intervention did not entail significant differences in anticholinergic deprescribing between the groups.
Zuerst veröffentlicht: 15. August 2025